Hegemony Culture Seen In Kate Elizabeth Russell's My Dark Vanessa - Suri, Elok Dita; Wahyono, Danu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
Abstract. This study analyzes the hegemony reflected in Kate Elizabeth Russell's novel My Dark Vanessa. It reveals how hegemonic power is manifested through the manipulation of Vanessa Wye, a young student who becomes a victim of oppression, by Jacob Strane, an influential teacher. The research aims to achieve two subjectives: to identity and describe the dominant and subordinate roles of the characters in My Dark Vanessa. The scope of this study is limited to cultural hegemony and focuses on a textual analysis of the characters’ interactions in the novel. The importance of this research is to shed light on the complexities of power and student victimization in education. A descriptive qualitative research design is used, involving the gathering and analyzing of data that are not numerical but describe data related to the research topic. The study employs the cultural hegemony, underscores how hegemony affects her ability to maintain social connections, navigate personal relationships, and understand her self concept in coping with her trauma. This research contributes to the discourse on mental health and power representation in literature and demonstrates the value of a sociological approach in unpacking complex character relationships. It provides a foundation for future studies on the intersection of power and literary analysis, enriching both academic and practical perspectives on hegemony. The findings reveal that her subordination is triggered by both psychological manipulation and societal norms, such as the romanticization of teacher and student relationships. Her experiences highlight the debilitating nature of hegemonic control. Keywords: Domination, Hegemony, Power, Roles, Subordination.